Simultaneous recovery of a locally rough interface and the embedded obstacle with its surrounding medium. (1st April 2022) - Yang, Jiaqing; Li, Jianliang; Zhang, Bo
Abstract: Consider the problem of scattering of time-harmonic point sources by an infinite locally rough interface with bounded obstacles embedded in the lower half-space. The model problem is first reduced to an equivalent integral equation formulation defined in a bounded domain, where the well-posedness is obtained in L p by the classical Fredholm theory. Then a global uniqueness theorem is proved for the inverse problem of recovering the locally rough interface, the embedded obstacles and the wave number in the lower-half space by means of near-field measurements above the interface.